Early prediction of Alzheimer's disease using convolutional neural network - Abed, Mahjabeen Tamanna; Nabil, Shanewas Ahmed; Fatema, Umme (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.